Taxonomic revision of Ediacaran tubular fossils: Cloudina, Sinotubulites and Conotubus. (March 2022) - Yang, Ben; Warren, Lucas V.; Steiner, Michael; Smith, Emily F.; Liu, Pengju
Abstract: The Ediacaran tubular fossils Cloudina, Sinotubulites, and Conotubus are taxonomically revised with type materials. It is proposed that Aulophycus lucianoi Beurlen and Sommer, 1957, is not a senior synonym of Cloudina hartmannae Germs, 1972 . Instead, most of its syntypes may be assigned to Sinotubulites or other taxa. Lectotypes of Sinotubulites baimatuoensis Chen et al., 1981, and Conotubus hemiannulatus Zhang and Lin in Lin et al., 1986, are designated from rediscovered syntypes. Sinotubulites baimatuoensis Chen et al., 1981, is reported from the Mooifontein Member of Nama Group at Aar Farm, Namibia. Cloudina waldei Hahn and Pflug, 1985, is assigned to Sinotubulites baimatuoensis, and thus its occurrence range is extended to Brazil. The lectotype of Conotubus hemiannulatus shows corrugations and annulations on the surface distinguishing it from Cloudina and other collared Ediacaran tubular fossils. Based on the taxonomic revision, we propose a Cloudina hartmannae Interval Zone for the terminal Ediacaran with the upper boundary defined by the first appearance datum of Protohertzina anabarica (i.e., the index fossil of the early Cambrian Anabarites trisulcatus - Protohertzina anabarica Assemblage Zone).